Capacity building for school improvement : revisited - Stringer, Patricia (Contemporary approaches to research in learning innovations, 2013)
At a time when there is a high demand for capacity building in schools, many administrators and practitioners find little if any empirical studies on how this can be achieved in practice. Through the eyes of an experienced researcher, schoolteacher, senior administrator and university lecturer, this book captures how a low decile school in New Zealand successfully built its capacity for improvement. Dr. Patricia Stringer allows the reader, who could be anyone with an interest in education, leadership and school development, to identify contextual problems and difficulties that limit capacity building and suggests pathways to overcome them. This is an easy to read and enjoyable book, but, one that digs deep into practice. The researcher spent over a year working with the staff, board and parents of this school discovering and recording authentic information about this schools successful journey to success. For the researcher, this was an exciting experience; one that needs to be shared with the wider educational community. A must read book.